2012
DOI: 10.1016/j.mambio.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Wolf (Canis lupus) feeding habits during the first eight years of its occurrence in Germany

Abstract: a b s t r a c tDue to the fact that the feeding habits of large carnivores are the main contentious point when they start resettling regions they were absent from for several decades, the diet composition of the wolves in Germany was analysed from the beginning of this process. Wolves in Germany primarily feed on wild ungulates, which make up more than 96% of their diet. The dominating prey species is the roe deer (55.3%), followed by red deer (20.8%) and wild boar (17.7%). The second important food category a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 46 publications
6
56
2
12
Order By: Relevance
“…Roe deer, red deer and fallow deer were generally avoided and there was no dietary response to changes in prey density of either primary or secondary prey species. Other studies in Europe [69, 70, 71] support the results from our study, i.e., that when roe deer are available at sufficiently high densities, they usually constitute a major part of the prey and sometimes become the preferred prey species of wolves. However, the prey community characteristics in Scandinavia are different from those of central and southern Europe where large ungulates like moose are not present.…”
Section: Discussionsupporting
confidence: 90%
“…Roe deer, red deer and fallow deer were generally avoided and there was no dietary response to changes in prey density of either primary or secondary prey species. Other studies in Europe [69, 70, 71] support the results from our study, i.e., that when roe deer are available at sufficiently high densities, they usually constitute a major part of the prey and sometimes become the preferred prey species of wolves. However, the prey community characteristics in Scandinavia are different from those of central and southern Europe where large ungulates like moose are not present.…”
Section: Discussionsupporting
confidence: 90%
“…Differences in habitat type or road densities thus cannot explain the preference of MTAs. Because densities of wild ungulates, the main prey of wolves in Germany (Wagner, Holzapfel, Kluth, Reinhardt, & Ansorge, ), are high in all areas settled by wolves to date (Reinhardt & Kluth, ), it is also implausible that different prey densities could serve as an explanation. Overall, it is unlikely that habitat suitability alone was the primary driver for the strong initial selection for MTAs by wolves. The preference for MTAs may be partly explained with natal habitat preference.…”
Section: Discussionmentioning
confidence: 99%
“…Wolf diet strongly depends on the availability of prey species [70]. In Europe [71], [72], [73], as well as in North America [74], [75], [76], the preferred prey species are large wild ungulates.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a standard method, there are numerous factors influencing hunting success and thus the size of the hunting bag [79]. Secondly, recent studies have shown no negative influence on the hunting bag for wild ungulates in hunting districts in the Lausitz, where wolves have lived for the past 8 years [70]. Ungulate densities, especially for roe deer and wild boar, have increased during the last 50 years in Germany [79], [80].…”
Section: Discussionmentioning
confidence: 99%